2016
DOI: 10.21608/jpp.2016.45396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Rootstocks on Flowering, Fruiting and Yield of Kalamata and Dolce Olive Trees

Abstract: The present study was carried out through 2013 and 2014 seasons in a private orchard at Cairo/Alex. desert road on 21 years old Picholine, Frantoio, Mission, Manzanillo and Koroneiki olive rootstocks which were re-juveniled and top grafted at 2008 season by Kalamata and Dolce olive cultivars. Trees were planted at 6 × 6 meters planting distances, and grown in Sandy soil under drip irrigation system. The aim of the present study was carried out to investigate the effect of different rootstocks (Picholine, Frant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The ability of rootstock to increase nitrogen and magnesium in their scion could by more important characters due to save nitrogen fertilization and lower environment pollution which may be increased scion leaves and SPAD value in Picual and Coratina rootstocks. These compatibility results may be explain the previous results by Mofeed [ 8 ] who stated that, Kalamata cultivar grafted onto Picual rootstock recorded the highest increase in vegetative behavior (trunk diameter, tree height, shoot length) and fruiting characteristics (fruit set, yield) compared to Koroneiki and Manzanillo rootstocks which affected Kalamata growth and yield negatively. In this context, Laz [ 6 ] found that, Kalamata grafted into Picual rootstock exhibited more vegetative growth (number of leaves, leaf area) than Koroneiki rootstock under salinity stress.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The ability of rootstock to increase nitrogen and magnesium in their scion could by more important characters due to save nitrogen fertilization and lower environment pollution which may be increased scion leaves and SPAD value in Picual and Coratina rootstocks. These compatibility results may be explain the previous results by Mofeed [ 8 ] who stated that, Kalamata cultivar grafted onto Picual rootstock recorded the highest increase in vegetative behavior (trunk diameter, tree height, shoot length) and fruiting characteristics (fruit set, yield) compared to Koroneiki and Manzanillo rootstocks which affected Kalamata growth and yield negatively. In this context, Laz [ 6 ] found that, Kalamata grafted into Picual rootstock exhibited more vegetative growth (number of leaves, leaf area) than Koroneiki rootstock under salinity stress.…”
Section: Discussionsupporting
confidence: 79%
“…Choosing the appropriate rootstock for Kalamata cultivar has not received much attention from the scientific community. Rootstocks affected plant vigor, nutritional status and overcoming biotic and abiotic stress [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%